The effect of preceding race efforts on pacing and short-track speed skating performance - Konings, M. J.; Hettinga, F. J. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To examine whether preceding high-intensity race efforts in a competitive weekend affect pacing behavior and performance in elite short-track speed skaters. Methods: Finishing and intermediate lap times were gathered from 500-, 1000-, and 1500-m short-track speed skating world cups during the seasons 2011-2016. The effect of preceding races on pacing behavior and performance was explored using 2 studies. Study I: The effect of competing in extra races due to the repechage (Rep) system, leading to an increased number of high-intensity race efforts prior to the subsequent main tournament race, was explored (500-m, n=32; 1000-m, n=34; and 1500-m, n=47). Study II: The performance of skaters over the tournament days was evaluated (500-m, n=129; 1000-m, n=54; and 1500-m, n=114). For both analytic approaches, a 2-way repeated-measures analysis of variance was used to assess differences in pacing and performance within skaters over the races. Results: An additional number of preceding high-intensity race efforts due to the Rep system reduced the qualification percentage in the first main tournament race for the next stage of competition in all events (500-m, direct qualification =57.3%, Rep=25.0%; 1000-m, direct=44.2%, Rep=28.3%; and 1500-m, direct=27.1%, Rep=18.2%) and led to a decreased pace in the initial 2 laps of the 500-m event. By contrast, tournament day (Saturday vs Sunday) only affected the pacing behavior of female skaters during the 1500-m event. Conclusion: High-intensity race efforts earlier in the day affected pacing and performance of elite skaters, whereas the effect of high-intensity race efforts from the previous day seemed to be only marginal.